An advancement in developmental and reproductive toxicity (DART) risk assessment: evaluation of a bioactivity and exposure-based NAM toolbox - Mueller, Iris; Abdelkhaliq, Ashraf; Carmichael, Paul; Dent, Matthew; Feliksik, Marleen; Flatt, Luke; Houghton, Jade; Horcas Nieto, José M.; Jamalpoor, Amer; Kukic, Predrag; Malcomber, Sophie; Nicol, Beate; et al. (Frontiers in Toxicology, 2025)
Traditional chemical safety assessment involves identifying the lowest level of a chemical that impacts endpoints measured in standardized animal studies to establish human exposure limits. In vitro assays have shown promise in providing points of departure that can be protective of human health when combined with exposure predictions into a bioactivity:exposure ratio (BER). Using a combination of broad screening tools and DART-targeted assays, we previously demonstrated high biological coverage of this NAM toolbox against a list of DART-relevant genes and pathways. To fully transition to an animal-free paradigm, it is crucial to establish confidence that these in vitro assays sufficiently represent the DART toxicity mechanisms, ensuring a level of protection that is safe for non-pregnant adults, pregnant women, and fetal populations. In this proof-of-concept study, we have extended the toolbox to include additional in vitro and in silico tools and have performed an evaluation using 37 benchmark compounds across 49 exposure scenarios. According to existing regulatory opinions, 18 of these scenarios would be considered high-risk chemical exposures from a DART perspective. Our DART NAM toolbox approach identified 17 out of these 18 high-risk scenarios. We further investigated the impact of population-based changes in pregnancy and the fetus on internal exposures by evaluating human clinical data where available for the 37 compounds. In most instances, the variability resulting from pregnancy or gestational changes falls within the range of toxicokinetic variability observed in the general population. This work demonstrates that protective safety decisions can be made for DART without generating new animal test data.